2022
DOI: 10.1001/jamaophthalmol.2022.4566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic, Demographic, and Health Care Access Disparities With Severe Visual Impairment in the US

Abstract: ImportanceApproximately 13% of US adults are affected by visual disability, with disproportionately higher rates in groups impacted by certain social determinants of health (SDOH).ObjectiveTo evaluate SDOH associated with severe visual impairment (SVI) to ultimately guide targeted interventions to improve ophthalmic health.Design, Setting, and ParticipantsThis quality improvement study used cross-sectional data from a telephone survey from the Behavioral Risk Factor Surveillance System (BRFSS) that was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Because the NHATS sample was last replenished in 2015, it may also be underpowered to detect differences between racial and ethnic groups in the multivariable model, an issue that may be resolved with ongoing sample replenishment and oversampling of Black and Hispanic respondents. These findings build on the emerging work that has been published on social determinants of vision health and substantiate the need for additional research to disentangle individual- and community-level factors that shape vision health outcomes and access to eye care.…”
Section: Discussionsupporting
confidence: 61%
“…Because the NHATS sample was last replenished in 2015, it may also be underpowered to detect differences between racial and ethnic groups in the multivariable model, an issue that may be resolved with ongoing sample replenishment and oversampling of Black and Hispanic respondents. These findings build on the emerging work that has been published on social determinants of vision health and substantiate the need for additional research to disentangle individual- and community-level factors that shape vision health outcomes and access to eye care.…”
Section: Discussionsupporting
confidence: 61%
“…Data sets may exclude populations from diverse racial and ethnic backgrounds or with low incomes. In the current work, for example, Besagar et al highlight that 76% of the sample were non-Hispanic White. People from racial and ethnic minority backgrounds and people with lower socioeconomic status are disproportionately affected by social risk factors.…”
mentioning
confidence: 61%
“…Large data sets, such as the Behavioral Risk Factor Surveillance System, are publicly available, providing a nationwide sample to evaluate health disparities, perform longitudinal surveillance, and identify areas of needed policy interventions. In this current work, the team found that severe visual impairment was associated with identifying as Black/African American, American Indian or Alaska Native, or Hispanic, having depression, being single, having poor economic stability, having low educational attainment, and having poor health care accessibility …”
mentioning
confidence: 78%
See 2 more Smart Citations